(untitled) (Al Basirah, 2020)
Islam and the West is a common term generally used for the two different and notable civilizations of the World. Most of the people are actually not aware of the real connotation and perspective of this term and of mutual interaction and encounter of the two. This paper studies the historical contact of Islam and the west and gives a comprehensive account on the subject. It finds that the interaction of Islam and the West was and has been inimical and uncongenial. The real cause of this hostility is the irrefutable and indefensible historical prejudices of the West against Islam and Muslims. To perish this mutual repugnance west will have to bring itself out from this bias. However some of the present day Muslims, who have taken on aggressive approaches and attitudes towards the west, also have to bring themselves out from their unislamic lookouts and acts.